Repeated sprint ability in young football players according to the position and formation of the team: the effect of a specific training program - Samolis, V.; Koutlianos, N.; Michailidis, Y.; Mandroukas, A.; Christoulas, K.; Metaxas, T. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The aim of this study was to investigate the effect of a specific training program for 12-weeks (twice a week) on the repeated sprint ability (RSA), according to the position of the football player in the formation of the team. METHODS: Two groups of U-17 football players (experimental-group, N.=22 and control-group, N.=19) and five positions (central-defenders, wide-defenders, central-midfielders, wingers, and central-attackers) according to the position in the formation (1-4-3-3) were studied. Sexual maturation was classified according to Tanner`s stages. RSA and isokinetic strength were measured pre- and after the training program. RESULTS: The results showed that in RSA were differences in the factor time in the best (F=9.316, n2=0.383, P=0.008) and mean time (F=8.002, n2=0.348, P=0.013), but there were no differences between the groups. In strength, differences were observed in the time, mostly in the extensors at the three angular velocities (60°, 180°, 300°·sec-1) with differences in the group only in the maximum force (F=8.090, n2=0.366, P=0.013). No differences between players` positions were observed. CONCLUSIONS: A specific training program seems to affect players` performance on repeated sprint ability and the specific training in the players` position according to the team formation has a positive effect on the muscle power of football players.